Government Expenditure and Economic Growth : An Empirical Investigation. (IMF Working Papers; Working Paper ;, 1989)
This paper examines the empirical evidence on the contribution that government and, in particular, capital expenditure make to the growth performance of a sample of developing countries. Using the Denison growth accounting approach, this study finds that social expenditures may have a significant impact on growth in the short run, but infrastructure expenditures may have little influence. While current expenditures for directly productive purposes may exert a positive influence, capital expenditure in these sectors appears to exert a negative influence. Experiments with other explanatory variables confirm the importance of the growth of exports to the overall growth rate.